(untitled) (Jurnal Riset Akuntansi dan Bisnis Indonesia, 2025)
This study aims to show the realization of groundwater tax revenue from the Platinum Adisucipto Hotel Yogyakarta in 2019-2023, To find out how the potential of the groundwater tax at the Platinum Hotel Adisucipto Yogyakarta, To find out the contribution of groundwater tax at the Platinum Hotel Adisucipto Yogyakarta to groundwater taxrevenue in the Sleman Regency Area in 2019-2023 and to explain the pace of growth from the groundwater tax of Hotel Paltinum Adisucipto Yogyakarta in 2019-2023. The data collection method used in this study is to use secondary data in the form of document studies by analyzing and calculating existing data and processing data obtained from the Platinum Adisucipto Hotel Yogyakarta in 2019-2023. The results of this study show that the amount of groundwater tax owed at the Platinum Hotel Yogyakarta in general shows an increase, while the growth rate of groundwater tax in 2019-2023 is said to be not good because it is still fluctuating. Meanwhile, the contribution to the groundwater tax of the Platinum Hotel to the groundwater tax revenue of Sleman district is not so large because indeed the number of hotels in Sleman district is quite large so that the level of contribution is fairly evenly distributed.